2014
DOI: 10.2169/internalmedicine.53.0649
|View full text |Cite|
|
Sign up to set email alerts
|

Renal and Vascular Protective Effects of Ezetimibe in Chronic Kidney Disease

Abstract: Objective Dyslipidemia is a risk factor for not only cardiovascular diseases (CVD), but also chronic kidney disease (CKD). Ezetimibe, a cholesterol absorption inhibitor, lowers cholesterol levels by inhibiting both extrinsic and intrinsic cholesterol absorption via the gastrointestinal duct. However, very few studies have examined its efficacy and safety for patients with dyslipidemia complicated with CKD. Methods Thirty-seven dyslipidemic patients (low density lipoprotein cholesterol (LDL-C) levels ! 120 mg/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Morita et al [3] have also reported that ezetimibe can be administered safely to CKD patients, and that it improved lipid profiles and decreased proteinuria and arterial stiffness. Ezetimibe may lower proteinuria and urinary L-FABP levels and improve vascular function via its lipid-lowering action, although the actual mechanisms remain to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…Morita et al [3] have also reported that ezetimibe can be administered safely to CKD patients, and that it improved lipid profiles and decreased proteinuria and arterial stiffness. Ezetimibe may lower proteinuria and urinary L-FABP levels and improve vascular function via its lipid-lowering action, although the actual mechanisms remain to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…In turn, 79 % of patients in Group C had been administered ezetimibe. Since ezetimibe would have renal protective effect [17, 18], it is likely that ezetimibe might be reno-protective as much as atorvastatin in this study [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…The Table 3 describes the effects of ezetimibe and the treatment indications for patients with renal disease. According to KDIGO guidelines [37], ezetimibe monotherapy is not recommended in CKD patients since there is only scarce evidence of its effectiveness on relevant clinical outcomes [103,104]. Conversely, mainly based on the results of the randomised double-blind SHARP (Study of Heart and Renal Protection) trial [33], the use of statin/ ezetimibe association is formally recommended in predialysis CKD patients (see above and Table 2).…”
Section: Statinsmentioning
confidence: 99%